Contribution of the Technological monitoring to the formulation of Projects of New Technologies for biofuels production - González Suárez, Erenio; González Cortés, Meilyn; Mesa Garriga, Leyanis; Villanueva Ramos, Gretel; Daniela Romano, Silvia; García Alaric, Romel (Centro Azúcar Journal, 2008)
A strategy is developed for the technology assimilation, through the formulation of investigation projects, for the development of New Technologies of biofuels obtaining, for that which the Technological monitoring was used as support tool to the formulation of Projects. The above-mentioned allows prevent the limitations of the existent technologies, as well as the possibilities to use new raw matters for Biofuels in the IberoAmerican context. As a result of the study it was obtained that the future in the development of these products heads to an economy based on the bioproducts, economy based on the biotechnology and that it uses renewable matters to obtain products and energy, as well as the formulation of 7 strategic projects for the biofuels obtaining in the Ibero-American context.